Evaluasi Pencegahan dan Penanggulangan Gizi Buruk Melalui PMT-P Balita di Desa Cikanyere Kabupaten Cianjur - Tuti Gantini; Kelik Putranto; Siti Muftiah (AGRITEKH (Jurnal Agribisnis dan Teknologi Pangan), 2022)
Children 1-4 years of age group are particularly vulnerable to nutritional diseases, such as vitamin A deficiency disease morbidity and protein energy malnutrition (MEP). Weight loss is one of the parameters which give a picture of the body mass. Body mass is very sensitive to sudden changes, such as infectious disease, decreased appetite or decreasing the amount of food consumed. To lower the malnutrition status in infants and toddlers can be done by providing fortification, supplementation of vitamins and minerals or Feeding Recovery (PMT - P). The program of PMT - P for toddler is one step that can be done in an effort to improve the nutritional intake of toddler food for optimal growth. This Research took place In Cempaka Putih, Cikanyere village of Cianjur. The objective of the research was to evaluate the effect that arises as a result of supplementary feeding recovery (PMT - P) on the growth of Toddlers weight. The samples in this study were infants aged 12-53 months as many as 30 infants, with a sampling technique using Porpusive Sampling. Data was analyzed statistically by the t-test. The results showed that the recovery of supplementary feeding in infants aged 12-53 months in the Cikanyere village of Cianjur significant effect on weight gain.